Draft Sequencing of the Heterozygous Diploid Genome of Satsuma (Citrus unshiu Marc.) Using a Hybrid Assembly Approach - Shimizu, Tokurou; Tanizawa, Yasuhiro; Mochizuki, Takako; Nagasaki, Hideki; Yoshioka, Terutaka; Toyoda, Atsushi; Fujiyama, Asao; Kaminuma, Eli; Nakamura, Yasukazu (Frontiers in Genetics, 2017)
Satsuma (Citrus unshiu Marc.) is one of the most produced mandarin varieties of citrus, with importance for seedless fruit production and as a breeding parent of citrus. De novo assembly of the heterozygous diploid genome of Satsuma (‘Miyagawa Wase’) was conducted by a hybrid assembly approach using short-read sequences, three mate-pair libraries, and a long-read sequence of PacBio by the PLATANUS assembler. The assembled sequence, with a total size of 359.7 Mb at the N50 length of 386,404 bp, consisted of 20,876 scaffolds. Pseudomolecules of Satsuma constructed by aligning the scaffolds to three genetic maps showed genome-wide synteny to the genomes of Clementine, pummelo and sweet orange. Gene prediction by modeling with MAKER-P proposed 29,024 genes and 37,970 mRNA, and gene prediction analysis found candidates for novel genes in several biosynthesis pathways for gibberellin and violaxanthin catabolism. The BUSCO scores for the assembled scaffold and predicted transcripts and another analysis by BAC end sequence mapping indicated the assembled genome consistency was close to those of the haploid Clementine, pummelo and sweet orange genomes. The numbers of repeat elements and long terminal repeat retrotransposon were comparable to those of the seven citrus genomes, and it suggested no significant failure in the assembly at the repeat region. A resequencing application using the assembled sequence confirmed that both kunenbo-A and Satsuma are offspring of Kishu, and Satsuma is a back-crossed offspring of Kishu. These results illustrated the performance of the hybrid assembly approach and its ability to construct an accurate heterozygous diploid genome.